Evaluating specialized knowledge for teaching statistics and probability: construction and validation of an MTSK-Stochastic Questionnaire - Franco Seguí, Joan (2023)
[Objective] This research presents the process of construction and validation of an MTSK-Stochastic Questionnaire. [Methodology] Through a process consisting of three phases – 1) bibliographic review; 2) construction of the initial version; 3) validation through expert judgment and subsequent implementation of the pilot (trial) – an open questionnaire was constructed to assist in gathering data for analysis and evaluation of aspects of specialized knowledge of in-service Primary Education teachers for teaching statistics and probability, based on the Mathematics Teacher’s Specialized Knowledge (MTSK) model and the Mathematics Teaching Itinerary Approach (MTIA). [Results] The evaluations and opinions of the experts were generally positive, although some elements of the initial questionnaire were eliminated and others were reformulated to improve clarity and ease of understanding. [Conclusions] The final version of the questionnaire, which consists of 5 items for the analysis of statistics and 5 items for the evaluation of probability, makes it possible to provide accurate evaluations of mastery of mathematical knowledge: knowledge of topics, mathematical structure, and mathematical practice; and, in the didactic domain, accurate evaluations of knowledge of learning standards and characteristics, as well as knowledge about mathematics teaching.